Sengketa Tanah Puri Asih Sejahtera: Pertentangan Keadilan Substantif dan Kepastian Formal dalam Hukum Agraria dan Kontrak - Astari Silmy (Jurnal Hukum Lex Generalis, 2026)
The Puri Asih Sejahtera housing land dispute (Bekasi) reveals a fundamental dilemma between formal legal certainty and substantive justice within Indonesia's agrarian legal system. Residents who had fully paid for their properties and occupied them for 34 years (1983-2018) were nevertheless evicted because they only held a Sale and Purchase Binding Agreement (PPJB), while the new developer (PT TPI) won the case based on the ne bis in idem principle. This study aims to analyze the weaknesses of the layered land registration system, the contradiction between Supreme Court Circular Letter (SEMA) No. 4/2016 (which recognizes a fully paid PPJB as a basis for substantive justice) and the application of the ne bis in idem principle, and to formulate legal protection recommendations for housing consumers. The method used is normative legal research with a case and statutory approach. The novelty lies in identifying the direct conflict between two legal instruments in Indonesian judicial practice. The results show that the negative-publicity system tending toward positive, layered formalities (PPJB-AJB-Certificate of Ownership), and the expansive interpretation of ne bis in idem have harmed good-faith buyers. Main recommendations include: (1) simplifying the system by integrating PPJB and AJB; (2) more progressive application of SEMA No. 4/2016; (3) government mediation and compensation/relocation; and (4) regulatory reform to provide legal certainty for fully paid buyers.